1997
DOI: 10.1007/s001670050048
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of high-frequency electrosurgery of the meniscus

Abstract: In an in vitro study of the sheep's meniscus, the possibilities to reduce the thermal tissue necrosis caused by high-frequency electrosurgery of the meniscus were studied. Under standardized conditions, machine-made sections through the meniscus were cut using electrodes of various thicknesses and different settings of the electric generator. The thermal tissue necrosis near the cut through the meniscus was determined using light microscopy and image analysis on the specimen stained according to Masson-Goldner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Previous experiments have shown the average thermal change produced by lasers or electrosurgical devices on the meniscus to range from a depth of 24 to 1980 m. 4,7,10,[12][13][14] Vangsness et al 14 measured thermal change in the human meniscus with several laser systems and found depths of change ranging from 96 (excimer) to 1980 (carbon dioxide) m. Sherk et al, 13 in a report on laser-induced thermal change, found a range of 24 (excimer) to 378 (neodynium:yttrium-aluminum-garnet) m. The depth of thermal change produced by the electrosurgical radiofrequency devices in this series was comparable with reported values in the literature on other lasers or electrosurgical devices. Recent work has demonstrated time-zero thermal change in the human meniscus to average around 550 m with a bipolar radiofrequency energy device.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown the average thermal change produced by lasers or electrosurgical devices on the meniscus to range from a depth of 24 to 1980 m. 4,7,10,[12][13][14] Vangsness et al 14 measured thermal change in the human meniscus with several laser systems and found depths of change ranging from 96 (excimer) to 1980 (carbon dioxide) m. Sherk et al, 13 in a report on laser-induced thermal change, found a range of 24 (excimer) to 378 (neodynium:yttrium-aluminum-garnet) m. The depth of thermal change produced by the electrosurgical radiofrequency devices in this series was comparable with reported values in the literature on other lasers or electrosurgical devices. Recent work has demonstrated time-zero thermal change in the human meniscus to average around 550 m with a bipolar radiofrequency energy device.…”
Section: Discussionmentioning
confidence: 99%
“…zu ersetzen. In verschiedenen Studien wurden diese Methoden untersucht und miteinander verglichen [30,31].…”
Section: Operationen An Den Meniskenunclassified